JOURNAL OF GOVERNMENT & POLITICS : New Public Management or Mismanagement? The Case of Public Service Agency of Indonesia - Jin-Wook Choi (FISIPOL UMY, 2016)
In line with the new public management (NPM), ap public service agency (PSA) is considered as an alternative to replace the government-led public service delivery in a more efficient and effective way.